2014
DOI: 10.1080/09658211.2014.921713
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electroencephalography neurofeedback training on episodic memory: A randomized, sham-controlled, double-blind study

Abstract: The relationships between memory processes and oscillatory electroencephalography (EEG) are well established. Neurofeedback training (NFT) may cause participants to better regulate their brain EEG oscillations. The present study is a double-blind sham-controlled design investigating the effect of NFT on memory. NFT included up-training upper alpha (UA) band, up-training sensory-motor rhythm (SMR) band and sham protocol. Thirty healthy adult volunteers were randomly divided into three treatment groups. NFT sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…So, future research is warranted to further elaborate in a systematic manner on the potential impact of potential confounding factors (e.g., small sample sizes such as in Rasey et al 1995, see below for more details on confounding factors). Besides that, as suggested earlier by Gruzelier (2014b, c), placebo is still rarely used as we encountered it in only six studies (i.e., Bazanova et al 2013;Escolano et al 2014;Guez et al 2015;Hsueh et al 2016;Kober et al 2015;Wang and Hsieh 2013) to demonstrate the statistical superiority of the effect on the NFB training. However, according to the guidelines for the evaluation of clinical efficacy of psychophysiological interventions, the inclusion of control and placebo or sham feedback groups would enhance the validity within the current research field on NFB training (La Vaque et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…So, future research is warranted to further elaborate in a systematic manner on the potential impact of potential confounding factors (e.g., small sample sizes such as in Rasey et al 1995, see below for more details on confounding factors). Besides that, as suggested earlier by Gruzelier (2014b, c), placebo is still rarely used as we encountered it in only six studies (i.e., Bazanova et al 2013;Escolano et al 2014;Guez et al 2015;Hsueh et al 2016;Kober et al 2015;Wang and Hsieh 2013) to demonstrate the statistical superiority of the effect on the NFB training. However, according to the guidelines for the evaluation of clinical efficacy of psychophysiological interventions, the inclusion of control and placebo or sham feedback groups would enhance the validity within the current research field on NFB training (La Vaque et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Beta augment NFB training can be used to enhance attentional processing . And more recent research has shown that SMR augment training can enhance attentional (Doppelmayer and Weber 2011;Gruzelier 2001, 2004;Fritson et al 2008) and declarative memory performance (Hoedlmoser et al 2008), facilitate semantic processing in a working memory task and familiarity-based processes in working memory (Guez et al 2015), improve surgical technique while considerably reducing time on task , and reduce sensorimotor interference . Finally, augment gamma NFB training was positively correlated with a decrease of selectively retrieving binding costs and an increase in intelligence score (Keizer et al 2010a, b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, increasing UA showed improvement in cognitive abilities and performance (Zoefel et al 2010), and improvement in certain forms of memory (Escolano et al 2011;Guez et al 2014;Hanslmayr et al 2005;Vernon et al 2009;Zoefel et al 2011). Applying SMR showed significantly enhancement in attention Gruzelier 2001, 2004;Vernon et al 2003).…”
Section: Introductionmentioning
confidence: 91%